Technical report: the comparison between the exponential growth model and hyperbolic growth model by using Indonesia population / Dayang Hasmera Emylia Mohd Zaki, Noor Shalifa Shaharudin and Nor Amira Amizan - Mohd Zaki, Dayang Hasmera Emylia; Shaharudin, Noor Shalifa; Amizan, Nor Amira (2016)
This study focused on the comparison between Exponential Growth Model and Hyperbolic Growth Model by using Indonesia population. The objectives of this project are to find the best model that can estimate the population of Indonesia in particular time, to apply the actual number of population in Indonesia by using Exponential Growth and Hyperbolic Growth models and also to compare the actual and approximate values using Exponential Growth and Hyperbolic Growth models. The secondary data are collected from the World Development Indicators (WDI) on April 2016. The estimated data are calculated with the help of Maple Software. The case study of this project is concentrated on the comparison between 2 years interval. The percentage of errors between actual data and the estimated data are also calculated. The results showed, the Hyperbolic Growth Model is better compared to Exponential Growth Model as the accuracy of the data is closer to the actual data. The results also showed, the data calculated by using Hyperbolic Growth Model have a less error compared to the Exponential Growth Model.